ACCOUNTING TREATMENT OF MURABAHAH IN SHARIA KPR FINANCING IN TERMS OF PSAK NO. 102 AT BANK SYARIAH INDONESIA BRANCH MEDAN PADANG BULAN - Azmelia, Elisya; Nasution, Anggi Pratama; Arnita, Vina (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This research is entitled "Accounting for Murabahah in Islamic Mortgage Financing in terms of PSAK No. 102 at Bank Syariah Indonesia Branch Medan Padang Bulan". This study aims to implement the murabahah contract on Sharia mortgages and the conformity of PSAK No. 102 Revision 2019 regarding murabahah accounting at Bank Syariah Indonesia Branch Medan Padang Bulan. This research uses descriptive qualitative method. The data collection technique in this study was in the form of interviews and some data obtained from Bank Syariah Indonesia Branch Medan Padang Bulan. The results of the research on the application of the murabahah contract on Sharia mortgages have been in accordance with what has been determined. Meanwhile, the implementation of murabahah financing is not fully in accordance with PSAK No. 102 Revision 2019 at Bank Syariah Indonesia Branch Medan Padang Bulan such as banks only apply murabahah financing based on orders only, meaning that, in PSAK 102 it is stated that murabahah can be carried out based on orders or without orders, in fact At Bank Syariah Indonesia Medan Padang Bulan Branch only applies murabahah based on order only.